Infection and colonization of rice seedlings by the plant growth-promoting bacterium Herbaspirilum seropedicae Z67 - James, Euan K.; Gyaneshwar, Prasad; Mathan, Natarajan; Barraquio, Wilfredo L.; Reddy, Pallavolu M.; Iannetta, Pietro P. M.; Olivares, Fabio L.; Ladha, Jagdish K. (Scientific Societies, 2002)
A β-glucoronidase (GUS)-marked strain of Herbaspirillum seropedicae Z67 was inoculated onto rice seedling cvs. IR42 and IR72. Internal populations peaked at over 106 log CFU per gram of fresh weight by 5 to 7 days after inoculation (DAI) but declined to 103 to 104 log CFU per gram of fresh weight by 28 DAI. GUS staining was most intense on coleoptiles, lateral roots, and at the junctions of some of the main and lateral roots. Bacteria entered the roots via cracks at the points of lateral root emergence, with cv. IR72 appearing to be more aggressively infected than cv. IR42. H. seropedicae subsequently colonized the root intercellular spaces, aerenchyma, and cortical cells, with a few penetrating the stele to enter the vascular tissue. Xylem vessels in leaves and stems were extensively colonized at 2 DAI but, in later harvests (7 and 13 DAI), a host defense reaction was often observed. Dense colonies of H. seropedicae with some bacteria expressing nitrogenase Fe-protein were seen within leaf and stem epidermal cells, intercellular spaces, and substomatal cavities up until 28 DAI. Epiphytic bacteria were also seen. Both varieties showed nitrogenase activity but only with added C, and the dry weights of the inoculated plants were significantly increased. Only cv. IR42 showed a significant (approximately 30%) increase in N content above that of the uninoculated controls, and it also incorporated a significant amount of 15N2.